Implication of MAPK, Lipocalin-2, and Fas in the protective action of liposomal resveratrol against isoproterenol-induced kidney injury - Ahlam M. Alhusaini; Samiyah M. Alshehri; Wedad S. Sarawi; Hanan K. Alghibiwi; Sumayya A. Alturaif; Reema A. Al khbiah; Shog M. Alali; Shaikha M. Alsaif; Ebtesam N. Alsultan; Iman H. Hasan (Elsevier, 2024)
Background and Objective: Isoproterenol (ISO) is a non-selective β-adrenergic receptor agonist. It can be used to treat bradycardia and cardiogenic shock. Despite its usefulness, the overstimulation of β-receptors by ISO can cause "cardiorenal syndrome," a term used to describe heart and kidney damage. Resveratrol (RES), a natural polyphenol, has marked anti-inflammatory and antioxidant activities. The present work was designed to study the protective efficacy of liposomal resveratrol (L-RES) against ISO-induced kidney injury. Materials and Methods: The kidney injury was induced in rats by administering ISO (50 mg/kg, s.c.) twice a week for 2 weeks. RES and L-RES were administered at a dose (20 mg/kg/ day, p.o.) along with ISO for 2 weeks. Inflammatory and apoptotic biomarkers were analyzed, which were validated using histochemical analysis. Results: ISO caused renal dysfunction, which manifested as elevated urea, creatinine and uric acid, besides cystatin c and MAPK protein overexpression. In addition, ISO induced gene expression of Fas and lipocalin-2 and provoked genomic DNA fragmentation in renal tissues as compared with the control group. Histological examination confirmed morphological alterations of the kidney tissues obtained from the ISO group. Concurrent treatment of either RES or L-RES with ISO significantly ameliorated kidney damage as demonstrated by the improvement of all measured parameters with the best results for L-RES. The histopathological findings were correlated with the above biochemical parameters. Conclusion: L-RES could be a promising approach for the prevention of kidney injury induced by ISO, most likely via the downregulation of MAPK, cystatin c, Fas, and lipocalin-2.